Mencetak Pendidik Berkualitas dalam Mencegah Radikalisme dan Kenakalan Remaja Melalui Pendekatan Qolb, Nafs dan Aql - Mohamad Aso Samsudin; Hasanah Hasanah (Fakultas Tarbiyah, Universitas Ibrahimy, 2022)
As human live in the world, certainly will not become out from problem live that keep coming back. Therefore, education comes as a one of media to solv life problems experienced by each individual through the empowering of cognitive, affective and psychomotor potentials. However, in its development, the path of education is not always excellent. The various problems regularly occur in the world of education, especially correlated with students’ immoral behavior. The role of the teacher as a key subject who has a more dominant portion of time to communicate with students is super vital in its existence to solve the problem of behavior deviation. Therefore, high quality of educators is needed. Educators, who are not only competent in utilizing cognitive potential but also proficient in preparing students with the noble character through deep understanding of the nafs, qolb and aql.